2022
DOI: 10.48550/arxiv.2206.09912
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Dense Representation Framework for Lexical and Semantic Matching

Abstract: Lexical and semantic matching capture different successful approaches to text retrieval and the fusion of their results has proven to be more effective and robust than either alone. Prior work performs hybrid retrieval by conducting lexical and semantic text matching using different systems (e.g., Lucene and Faiss, respectively) and then fusing their model outputs. In contrast, our work integrates lexical representations with dense semantic representations by densifying high-dimensional lexical representations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 37 publications
0
1
0
Order By: Relevance
“…Researchers have observed that LSR models and token-level dense models like ColBERT tend to generalize better than single-vector dense models on the BEIR benchmark [8,35]. There are also recent works proposing hybrid retrieval systems that combine the strength of both dense and sparse representations [3,18,19], which can bring benefits for both in-domain and out-of-domain effectiveness [19].…”
Section: Unified Learned Sparse Retrieval Frameworkmentioning
confidence: 99%
“…Researchers have observed that LSR models and token-level dense models like ColBERT tend to generalize better than single-vector dense models on the BEIR benchmark [8,35]. There are also recent works proposing hybrid retrieval systems that combine the strength of both dense and sparse representations [3,18,19], which can bring benefits for both in-domain and out-of-domain effectiveness [19].…”
Section: Unified Learned Sparse Retrieval Frameworkmentioning
confidence: 99%